A charge-separated diamondoid metal–organic framework. Issue 89 (24th October 2018) - Thapa, Sheela; Hettiarachchi, Eshani; Dickie, Diane A.; Rubasinghege, Gayan; Qin, Yang
Abstract : Metal–organic framework with diamondoid structure constructed with precisely placed tetrahedral borate anions and copper(i ) cations. Abstract : We report the synthesis, characterization, and gas adsorption analyses of a new charge-separated metal–organic framework (MOF), UNM-1 (C52 H16 BCuF16 N4 ), possessing diamondoid structures, assembled from an anionic tetrahedral borate ligand and cationic Cu(i ) metal ion. The resulting MOF structure displays four-fold interpenetration, resulting in high environmental stability, and at the same time possesses relatively large surface area (SABET = 621 m 2 g −1 ) due to the absence of free ions. Gas adsorption measurements revealed temperature-dependent CO2 adsorption/desorption hysteresis and large CO2 /N2 ideal selectivities up to ca. 99 at 313 K and 1 bar, suggesting potential applications of this type of charge-separated MOFs in flue gas treatment and CO2 sequestration.